동일 환자에서 시행한 슬관절 단일구획 치환술과 전치환술의 생존율 비교 - 김경태(Kyung Tae Kim); 이송(Song Lee); 김지형(Jee Hyoung Kim); 정진(Jin Jung); 최원준(Won Jun Choi) (The journal of the Korean Orthopaedic Association, 2022)
목적: 퇴행성 슬관절염 환자에서 양측 슬관절에 단일구획 치환술과 전치환술을 각각 시행한 후 각 수술의 생존율을 알아보고 그결과를 비교하고자 했다. 대상 및 방법: 2002년 1월부터 2004년 12월까지 한 쪽 슬관절에는 단일구획 치환술을, 반대쪽 슬관절에는 전치환술을 시행받았던 51명의 퇴행성 슬관절염 환자들을 대상으로 수술 후 실패의 원인을 알아보고 Kaplan–Meier 방법을 사용해 각 수술의 생존율을 측정했고 Stratified Cox proportional hazard regression for matched-pair analysis를 사용해 상호 유의성을 검증하고 위험도를 비교했다. 수술은 동일 입원 기간 중 1주일 간격으로 시행했으며 수술 시 평균 연령은 64.2세였고 평균 추시 기간은 12.7 년이었다. 결과: 수술 후 실패는 슬관절 단일구획 치환술에서 13예(25.5%), 전치환술에서 3예(5.9%) 등 총 16예에서 발생했다. 실패의 원인은 단일구획 치환술에서는 치환물의 해리 4예(7.8%), 가동성 삽입물의 탈구 3예(5.9%), 외측 구획 퇴행성관절염 3예(5.9%), 감염 1예(2.0%)였고 원인 불명인 경우가 2예 있었다. 전치환술에서는 폴리에틸렌 삽입물의 마모로 인한 실패가 2예(3.9%), 감염으로 인한 실패가 1예(2.0%)였다. 삽입물의 단순 교환을 포함하여 재치환술을 시행한 경우를 실패로 정의했을 때 단일구획 치환술의10년 누적 생존율은 84.7%, 15년 누적 생존율은 69.6%였고 전치환술의 10년 누적 생존율은 97.9%, 15년 누적 생존율은 94.2% 였다. 두 군간의 생존율을 비교 분석한 결과 단일구획 치환술이 전치환술에 비해서 실패의 위험비가 3.7배 높았고 생존율이 통계적으로 유의하게 낮았다(p=0.046). 결론: 퇴행성 슬관절염 환자에서 양측 슬관절에 단일구획 치환술과 전치환술을 각각 시행했을 때, 단일구획 치환술의 실패의 위험비가 전치환술에 비해서 더 높았고 생존율도 유의하게 낮았다. 따라서 관절염의 정도와 범위, 환자의 연령 등을 고려하여 적절한수술 방법을 선택하는 것이 바람직할 것으로 판단된다. Purpose: To investigate and compare the survivorship of each surgery in patients with osteoarthritis of knees after performing unicompartmental knee arthroplasty (UKA) on one knee and total knee arthroplasty (TKA) on the other. Materials and Methods: From January 2002 to December 2004, 51 patients with osteoarthritis of knees who underwent UKA on one knee and TKA on the contralateral knee were investigated for the cause of postoperative failure if any, and the survival rate using the Kaplan–Meier method. The Stratified Cox proportional hazard regression for matched-pair analysis was used to verify mutual significance and compare risks. Surgery was performed at intervals of one week during the same hospitalization period. The mean age at surgery was 64.2 years and the mean follow-up period was 12.7 years. Results: Failures following the UKA occurred in 13 cases (25.5%). The causes of the failure included 4 cases of aseptic loosening, 3 cases of dislocation of mobile-bearing, 3 cases of lateral compartment osteoarthritis, 1 case of infection, and 2 cases of unknown cause. Failures following the TKA occurred in 3 cases (5.9%) including 2 cases of polyethylene wear and 1 case of infection. The cumulative survival rate of the UKA was 84.7% at 10 years and 69.6% at 15 years. The cumulative survival rate of the TKA was 97.9% at 10 years and 94.2% at 15 years. As a result of a comparative analysis of the survivorship between the two groups, it was observed that the risk of failure was 3.7 times higher in the UKA than in TKA, and there was a statistically significant difference in the survivorship (p=0.046). Conclusion: When UKA and TKA were performed on both knees in patients with osteoarthritis of knees, the risk of failure of UKA was higher than that of TKA, and the survivorship was also significantly lower. Therefore, it is desirable to select an appropriate surgical method taking into consideration the degree of arthritis, the age of the patient, and other similar factors. KCI Citation Count: 0